The cultural policy value of building social connection for new arrivals and why arts work evaluations should reflect that value. Issue 4 (7th June 2021) - Edmonds, Angelique; Roberts, Rosie
ABSTRACT: Increasing movement of migrants and refugees around the world present complex social issues for countries experiencing large migrant intakes. Support for recent arrivals needs deeper policy consideration, especially as reflected in cultural policy. Anecdotally, we know arts projects have greater success in assisting refugees to build social connections and support settlement than many formal government settlement programs. However, as arts initiatives struggle for adequate funding, evaluation's quantitative bias means that administrators face a conundrum about how to demonstrate evidence which values their work. Qualitative outcomes of supporting cultural expression, building trust, social connections and relationships are difficult to evidence, yet these make arts initiatives successful in supporting new arrivals. This paper discusses the context of that conundrum, explores the possibilities afforded by valuing social connection more highly and the consequences of such an approach. We argue that what is valued and how it is demonstrated need to be radically reconsidered.